2014
DOI: 10.5935/abc.20140162
|View full text |Cite
|
Sign up to set email alerts
|

Value of the Qrs-T Angle in Predicting the Induction of Ventricular Tachyarrhythmias in Patients with Chagas Disease

Abstract: BackgroundThe QRS-T angle correlates with prognosis in patients with heart failure and coronary artery disease, reflected by an increase in mortality proportional to an increase in the difference between the axes of the QRS complex and T wave in the frontal plane. The value of this correlation in patients with Chagas heart disease is currently unknown. ObjectiveDetermine the correlation of the QRS-T angle and the risk of induction of ventricular tachycardia / ventricular fibrillation (VT / VF) during electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In general, high QT dispersion values have been reported in patients with systemic HT and left ventricular hypertrophy (LVH) [16] . However, the pathophysiological mechanisms underlying repolarization abnormalities in patients with HT were partially explained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, high QT dispersion values have been reported in patients with systemic HT and left ventricular hypertrophy (LVH) [16] . However, the pathophysiological mechanisms underlying repolarization abnormalities in patients with HT were partially explained.…”
Section: Discussionmentioning
confidence: 99%
“…The QRS-T angle has recently been shown to be a strong and independent predictor of cardiac mortality for various patient groups such as coronary artery disease [5] , heart failure [7] , type 2 diabetes mellitus [14] , elderly subjects [6] , postmenopausal women [15] , and Chagas disease [16] . Nonetheless, studies investigating the role of the QRS-T angle in HT are limited.…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, however, the seminal report by Zabel et al, (2000) showed that the angle of the ventricular gradient, that is the 3-dimensional angle between the QRS and T wave orientations, is a potent predictor of mortality risk in survivors of acute myocardial infarction. Subsequently, the risk stratification strength of the QRS-T angle has been confirmed in a large number of studies including investigations of other ischaemic heart disease populations ( de Torbal et al, 2004 ; Malik et al, 2004 ), acute coronary syndrome ( Lown et al, 2012 ), heart failure ( Gotsman et al, 2013 ; Selvaraj et al, 2014 ; Sweda et al, 2020 ), hypertrophic ( Cortez et al, 2017a ; Cortez et al, 2017b ; Jensen et al, 2021 ) and dilated cardiomyopathy ( Li et al, 2016 ), diabetic patients ( Voulgari et al, 2010 ; Cardoso et al, 2013 ; May et al, 2017 ; May et al, 2018 ), renal patients on haemodialysis ( de Bie et al, 2013 ; Poulikakos et al, 2018 ); and many other populations and conditions ranging from systemic sclerosis ( Gialafos et al, 2012 ) and Chagas disease ( Zampa et al, 2014 ) to overall hospital ( Yamazaki et al, 2005 ) and general populations ( Kardys et al, 2003 ; Kors et al, 2003 ; Walsh et al, 2013 ). It has also recently been shown that QRS-T angle might be meaningfully combined with other ECG-based risk factors ( Hnatkova et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%